Compared Efficacy of Preservation Solutions in Liver Transplantation: A Long‐Term Graft Outcome Study From the European Liver Transplant Registry. Issue 2 (February 2015) - Adam, R.; Delvart, V.; Karam, V.; Ducerf, C.; Navarro, F.; Letoublon, C.; Belghiti, J.; Pezet, D.; Castaing, D.; Le Treut, Y. P.; Gugenheim, J.; Bachellier, P.; et al.
<x xml:space="preserve">Abstract</x> Between 2003 and 2012, 42 869 first liver transplantations performed in Europe with the use of either University of Wisconsin solution (UW; N = 24 562), histidine‐tryptophan‐ketoglutarate(HTK; N = 8696), Celsior solution (CE; N = 7756) or Institute Georges Lopez preservation solution (IGL‐1; N = 1855) preserved grafts. Alternative solutions to the UW were increasingly used during the last decade. Overall, 3‐year graft survival was higher with UW, IGL‐1 and CE (75%, 75% and 73%, respectively), compared to the HTK (69%) (p < 0.0001). The same trend was observed with a total ischemia time (TIT) >12 h or grafts used for patients with cancer (p < 0.0001). For partial grafts, 3‐year graft survival was 89% for IGL‐1, 67% for UW, 68% for CE and 64% for HTK (p = 0.009). Multivariate analysis identified HTK as an independent factor of graft loss, with recipient HIV (+), donor age ≥65 years, recipient HCV (+), main disease acute hepatic failure, use of a partial liver graft, recipient age ≥60 years, no identical ABO compatibility, recipient hepatitis B surface antigen (−), TIT ≥ 12 h, male recipient and main disease other than cirrhosis. HTK appears to be an independent risk factor of graft loss. Both UW and IGL‐1, and CE to a lesser extent, provides similar results for full size grafts. For partial deceased donor liver grafts, IGL‐1 tends to offer the best graft outcome.